Representasi Komunikasi Kelompok Suporter Sepak Bola Dalam Film Ultras - Omar Al Syahdi; Wiki Angga Wiksana (UNISBA Press, 2023)
Abstract. The film “Ultras” tells the story of a group of football fans from Italy who live a group life in favor of a football team. This study uses a semiotic methodology, which is to examine a sign. This research focuses on how the sociometric representation in group communication in the film